Przebieranka lekka i wytworna - Łukasiewicz, Jacek (1934-2021).; Kuryluk, Ewa (1946- ). (2008)
Recenzja książki: Wiek 21 / Ewa Kuryluk. Gdańsk, 1995.
Tytuł nagłówkowy.
Keywords: Książki -- recenzje -- 1990-.